Quality of life outcome in revision rhinoplasty in regards to number of revision surgeries and cartilage donor site - Riedel, Frank; Wähmann, Matthias; Veit, Johannes Adrian; Bulut, Cem (Auris, nasus, larynx, 2022)
Objectives - Rhinoplasty with or without combined septoplasty is one of the most frequently performed procedures in facial plastic surgery. Patient satisfaction and improvement in quality of life (QoL) is the primary goal. This prospective study was conducted to analyse Qol outcome in revision rhinoplasty in regards to number of revision surgeries and cartilage donor site using patient-reported outcome measures (PROMs). - Methods - Preoperative and at least 12-months postoperative scores on the Nasal Obstruction Symptome Evaluation (NOSE) questionnaire (range 0-100, lower scores indicate better outcome) and the Rhinoplasty Outcomes Evaluation (ROE) questionnaire (range 0-100, higher scores indicates better outcome) were obtained. Additionally, data on age, gender and number of previous rhinoplasties were assessed. All revision rhinoplasties were performed by one surgeon (author, F.R.) between 2014 and 2017. - Results - Sixty-four patients (11 (17.2%) male, 53 (82.8%) female) prospectively enrolled in this study. In 41 (64.1%) cases septal cartilage and in 23 (35.9%) patients ear cartilage was the donor site in revision surgery. Patients with more than one previous surgery (n=18) started with a lower preoperative ROE score (28.2 ± 12.8) compared to patients who had received only one previous surgery. The difference however was not significant (p=0.06). This subgroup still showed significant postoperative improvement (ROE-postop 61.9 ± 24.2; p<0.05). Both cohorts (septal cartilage and ear cartilage) improved significantly in regards to their ROE and NOSE scores after surgery and therefore showed improved health-related QoL. We could not detect any differences in health-related QoL postoperatively in regards to cartilage donor site in revision surgery. - Conclusion - Revision rhinoplasty improves health-related QoL. There are no differences in ROE- or NOSE-scores postoperatively in regards to graft material (ear- versus septal cartilage). Both subgroups show significantly higher scores postoperatively.